Variation of carbonate buffer and air- water (CO\(_2\)) flux in Ha Long Bay - Pham , Thi Kha; Cao , Thi Thu Trang; Le , Van Nam; Dinh, Hai Ngoc; Tran, Anh Tu (Vietnam Journal of Marine Science and Technology, 2025)
Investigations were carried out during the rainy and dry seasons of 2023–2024 in the Ha Long bay to evaluate composition of the carbonate buffer as well as the air-sea CO2 flux. The results showed that in the dry season, pH, temperature and salinity was higher than in rainy season. pH were from 7.68–8.33, average 8.25 in the dry season, 8.10 in the rainy season. Temperature were from 17.6–34.6oC, average 20.1oC in the dry season, 32.12oC in the rainy season. Sanility were from 15–31‰, average 30.7‰ in the dry season, 25 ‰ in the rainy season. DIC were from 41.91–58.77 mg/kg. TA were from 868.29–1,148.9 µmol/kg, average 1,105.98 µmol/kg in the dry season, 966.42 µmol/kg in the rainy season. The carbonate buffer in rainy season composed of HCO3- occupied from 87.42 to 88.02%, CO32- occupied from 11.67 to 12.20 %, CO2 occupied from 0.31 to 0.38%, and in dry season HCO3- occupied from 85.97 to 88.02%, CO32- occupied from 11.67 to 13.77 %, CO2 occupied from 0.26 to 0.31%. The partial pressure of CO2 (pCO2) in water in dry season were lower and less fluctuation in the rainy season. In dry season, pCO2 were from 81.75 to 169.84 µatm, average 99.16 µatm at day-night site and average 113.30 µatm at spatial sites. In rainy season, pCO2 were from 60.47 to 430.96 µatm, average 164.78 µatm at day-night site and average 134.28 µatm at spatial sites. The flux of CO2 exchange through the sea surface-air ranged from -13.0 to -7.4 mmol/m2/day, average -10.2 ± 1.0 mmol/m2/day at day-night site, average -11.6 ± 0.9 mmol/m2/day at spatial sites in rainy season; from -13.7 to -11.1 mmol/m2/day, average -12.9 ± 0.8 mmol/m2/day at day-night site and average 12.6 ± 0.6 mmol/m2/day at spatial sites in dry season. Thus, in the rainy season and dry season, Ha Long Bay acted as a sink for atmosphere CO2 and the CO2 flow rate in the dry season was higher than the rainy season.